2013
DOI: 10.1523/jneurosci.3256-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

BDNF-Dependent Recycling Facilitates TrkB Translocation to Postsynaptic Density during LTP via a Rab11-Dependent Pathway

Abstract: Brain-derived neurotrophic factor (BDNF) plays an important role in the activity-dependent regulation of synaptic structure and function via tropomyosin related kinase B (TrkB) receptor activation. However, whether BDNF could regulate TrkB levels at synapse during long-term potentiation (LTP) is still unknown. We show in cultured rat hippocampal neurons that chemical LTP (cLTP) stimuli selectively promote endocytic recycling of BDNF-dependent full-length TrkB (TrkB-FL) receptors, but not isoform T1 (TrkB.T1) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 58 publications
4
60
0
Order By: Relevance
“…However, BDNF and its propeptide have been found in presynaptic dense core vesicles, but not in the postsynaptic dendrites of the adult mouse hippocampus (6), suggesting an anterograde mode of action of BDNF. Previous work has shown that extracellular BDNF released by either pre-or postsynaptic neurons could be recycled back to the synaptic sites via binding to TrkB receptors on the dendrites of postsynaptic neurons (46,47). In the present work, we further showed that BDNF could be internalized and released at postsynaptic sites via physiologically Fig.…”
Section: Discussionsupporting
confidence: 68%
“…However, BDNF and its propeptide have been found in presynaptic dense core vesicles, but not in the postsynaptic dendrites of the adult mouse hippocampus (6), suggesting an anterograde mode of action of BDNF. Previous work has shown that extracellular BDNF released by either pre-or postsynaptic neurons could be recycled back to the synaptic sites via binding to TrkB receptors on the dendrites of postsynaptic neurons (46,47). In the present work, we further showed that BDNF could be internalized and released at postsynaptic sites via physiologically Fig.…”
Section: Discussionsupporting
confidence: 68%
“…In our previous studies, we found that Rab11 associates with TrkB-FL and mediates its postendocytic recycling (Huang et al, 2013). It has also been reported that Rab11 associates with Myo5a and mediates the trafficking cargos such as AMPA receptors (Correia et al, 2008;Roland et al, 2009;Lindsay et al, 2013).…”
Section: Rab11 Regulates the Interaction Between Myo5a And Trkb-flmentioning
confidence: 76%
“…Next, we investigated whether Myo5a participated in the postendocytic recycling of TrkB-FL. We used a live-cell ratiometric fluorescence-based recycling assay, which has been widely used in our previous studies (Chen et al, 2005;Huang et al, 2009;Huang et al, 2013), to measure the recycling levels of TrkB-FL (Fig. 4A).…”
Section: Myo5a Is Not Involved In Bdnf-dependent Trkb-fl Internalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, it was shown that PKG II interacts with GDP-bound Rab11b and that this interaction is crucial for their co-localization at the recycling endosome and their subsequent return to the plasma membrane (26). Rab11 has also been reported to interact with other membrane-associated proteins such as the ␤ 2 -adrenergic receptor, TRPV5 and TRPV6 Ca 2ϩ channels, b-isoform of the thromboxane A 2 receptor (TPb), and brain-derived neurotrophic factordependent TrkB (TrkB-FL) receptors (27)(28)(29)(30).…”
mentioning
confidence: 99%